THE POSITION OF THE SUPREME COURT RELATING TO THE PROTECTION OF THE FUNDAMENTAL RIGHTS OF THE CORPORATE CRIMINAL LIABILITY IN THE CRIMINAL PROCEEDINGS - García,Fernando Santa-Cecilia (2020)
Abstract The main idea behind this communication is to comment the Judgments of The Criminal Chamber of the Spanish Supreme Court, relating to how corporate criminal liability interacts with the criminal liability of the individuals within the company who may have committed a criminal offense. Several fundamental rights that have been studied in these sentences are analyzed in order to verify whether the corporate liability is protected by the same rights as the natural person. In particular, we will study whether the Fundamental Right of Defense, contained in the Spanish Constitution, is guaranteed to the corporate liability in the criminal procedure in the same way as to the natural person.